Snap-in interactions between water droplets and hematite/quartz surfaces with various roughness after conditioning with soluble starch and DDA using a dynamic microbalance. (February 2022) - Zhu, Zhanglei; Li, Zhen; Yin, Wanzhong; Yang, Bin; Qu, Jinzhou; Zhang, Ningning; Chen, Songjiang; Yu, Yuexian; Chang, Jing; Liu, Lijun
Highlights: Hematite and quartz surfaces with different roughness were conditioned with starch and DDA. Snap-in force of water droplets on the surfaces of the conditioned minerals was measured. The largest variation in snap-in force was presented on the roughest surface. Increasing roughness could enlarge the snap-in force difference for the two minerals. There is a liner correlation between snap-in force and advancing contact angle. Abstract: Surface roughness plays a vital role in flotation, because it has a pronounced impact on colloidal interactions, i.e., solid-liquid adhesion. In the previous studies, the natural mineral surfaces with various roughness were mainly taken as research object and the adhesion force of liquid on mineral surfaces with various roughness after conditioning with surfactants remains unknown. To fulfil this gap, in this study, the role of surface roughness in the snap-in force (An attractive force when the water droplet sharply and instantaneously spreads on the mineral surface in less than 0.1 s) of water droplets on hematite and quartz surfaces after conditioning with soluble starch and dodecylamine (DDA) was investigated using a high-sensitivity microelectronic mechanical balance. Results revealed that the effect of surface roughness on the snap-in force of water droplets on hematite surfaces was distinctly affected by the concentrations of both DDA and soluble starch, while the effect of surface roughness on the snap-in force of water droplets on quartz surfaces was only significantly affected by DDA concentration. After conditioning with 2 × 10 −4 mol/L soluble starch and 4 × 10 −4 mol/L DDA under pH value of 8.75, increasing surface roughness increased the snap-in force of water droplets on hematite surfaces and decreased the snap-in force of water droplets on quartz surfaces, suggesting that increasing surface roughness could enlarge the difference in the snap-in force of water droplets on the surfaces of the two minerals. In addition, the snap-in force was found to be a linear correlation with the advancing contact angle, providing evidence that surface roughness could affect the wettability and thereby the snap-in force.